Organic mononitrites of 1,2-propanediol act as an effective NO-releasing vasodilator in pulmonary hypertension and exhibit no cross-tolerance with nitroglycerin in anesthetized pigs - Nilsson KF; Goździk W; Frostell C; Zieliński S; Zielińska M; Ratajczak K; Skrzypczak P; Rodziewicz S; Albert J; Gustafsson LE (Dove Medical Press, 2018)
Kristofer F Nilsson,1,2 Waldemar Goździk,3 Claes Frostell,4 Stanisław Zieliński,3 Marzena Zielińska,3 Kornel Ratajczak,5 Piotr Skrzypczak,5 Sylwia Rodziewicz,5 Johanna Albert,6 Lars E Gustafsson1,† 1Department of Physiology and Pharmacology, Karolinska Institutet, Stockholm, Sweden; 2Department of Cardiothoracic and Vascular Surgery, Faculty of Medicine and Health, Örebro University, Örebro, Sweden; 3Department of Anaesthesiology and Intensive Therapy, Wroclaw Medical University, Wroclaw, Poland; 4Department of Anesthesia and Intensive Care, Danderyd Hospital, Stockholm, Sweden; 5Department and Clinic of Surgery, Wroclaw University of Environmental and Life Sciences, Wroclaw, Poland; 6Department of Surgery, Danderyd Hospital, Stockholm, Sweden †Lars E Gustafsson passed away on October 04, 2017 Purpose: Clinically available intravenous (IV) nitric oxide (NO) donor drugs such as nitroglycerin (GTN) cause systemic hypotension and/or tolerance development. In a porcine model, novel NO donor compounds – the organic mononitrites of 1,2-propanediol (PDNO) – were compared to GTN with regard to pulmonary selectivity and tolerance development. The vasodilatory effects of inorganic nitrite were investigated.Materials and methods: In anesthetized piglets, central hemodynamics were monitored. At normal pulmonary vascular resistance (PVR), IV infusions of PDNO (15–60 nmol kg-1 min-1), GTN (13–132 nmol kg-1 min-1), and inorganic nitrite (dosed as PDNO) were administered. At increased PVR (by U46619 IV), IV infusions of PDNO (60–240 nmol kg-1 min-1) and GTN (75–300 nmol kg-1 min-1) before and after a 5 h infusion of GTN (45 nmol kg-1 min-1) were given.Results: At normal PVR, PDNO (n=12) and GTN (n=7) caused significant dose-dependent decreases in mean systemic and pulmonary arterial pressures, whereas inorganic nitrite (n=13) had no significant effect. At increased PVR, PDNO (n=6) and GTN (n=6) significantly decreased mean systemic and pulmonary pressures and resistances, but only PDNO reduced the ratio between pulmonary and systemic vascular resistances significantly. After the 5 h GTN infusion, the hemodynamic response to GTN infusions (n=6) was significantly suppressed, whereas PDNO (n=6) produced similar hemodynamic effects to those observed before the GTN infusion.Conclusion: PDNO is a vasodilator with selectivity for pulmonary circulation exhibiting no cross-tolerance to GTN, but GTN causes non selective vasodilatation with substantial tolerance development in the pulmonary and systemic circulations. Inorganic nitrite has no vasodilatory properties at relevant doses. Keywords: nitrites, nitrates, nitric oxide donors, tachyphylaxis, PDNO